THE UNIQUENESS OF IMAM BUKHARI’S AND IMAM MUSLIM’S CRITERIA FOR SAHIH HADITH (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the science of hadith (Islamic tradition) and studies two of its most important collections – “Sahih al-Bukhari” and “Sahih Muslim”. The article provides a detailed analysis of the rigorous scientific criteria applied by Imam Muhammad ibn Ismail al-Bukhari and Imam Muslim ibn al-Hajjaj an-Nisaburi in compiling hadith collections. The paper discusses three main conditions established by Imam al-Bukhari for hadith selection – the authenticity of the hadith, requirements for narrators, and the continuity of the chain of transmission (isnad) in the form of “mu’anan” (transmission “from so-and-so from so-and-so”). It also demonstrates that Imam Muslim established similar but somewhat less stringent conditions. The research shows that Imam al-Bukhari applied twelve strict criteria, while Imam Muslim applied eleven criteria, which ensured that “Sahihayn” (the two authentic collections) received the status of the most reliable sources in Islamic scholarship after the Quran.
Keywords: Authentic hadith; Sahihayn; isnad; narrator; integrity; accuracy; mu‘an‘an